2020
DOI: 10.1007/s00217-020-03639-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of variety and weather conditions on fatty acid composition of winter and spring Camelina sativa varieties in Poland

Abstract: The aim of this study was to determine the influence of weather conditions over the course of 4 years (2016–2019) on the fatty acid profile of Camelina sativa. It was assumed that varieties and functional forms of plants (spring and winter genotypes) were characterized by a different fatty acid composition and that weather conditions affected the profile of fatty acids in camelina seeds. Statistical analyses were performed based on the results of chemical tests. Differences were found in the mean concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
2
7
1
Order By: Relevance
“…The significant variation in all the main FAs of Joelle oil reported in the present study differ from the results of Kurasiak-Popowska et al (2020a), which highlighted the high compositional stability of different winter and spring camelina lines grown in the same environment in Poland over three consecutive growing seasons.…”
Section: Discussioncontrasting
confidence: 96%
“…The significant variation in all the main FAs of Joelle oil reported in the present study differ from the results of Kurasiak-Popowska et al (2020a), which highlighted the high compositional stability of different winter and spring camelina lines grown in the same environment in Poland over three consecutive growing seasons.…”
Section: Discussioncontrasting
confidence: 96%
“…Our studied 136 DH lines derived from 15 different crosses helped us to find out the relationships between the seed yield and oil quality as a key factor to achieve high yielding cultivars with a favorable oil quality under rain-fed conditions. It is also noteworthy to mention the effect of maturation habitat as well as climatic conditions that may significantly affect the oil quality in oilseed crops [54,55]. Among our results there were robust correlations between SY and OC, and SY and DM (Figure 3).…”
Section: Discussionsupporting
confidence: 57%
“…It remains to be seen how plastic pennycress seed FA composition is under variable farm field conditions. Reports with other species in this regard have been mixed, with camelina varieties showing no variation in seed oil FA composition based on different weather conditions (Kurasiak-Popowska et al, 2021), whereas oilseed rape was found to have higher and lower seed oil linolenic acid content corresponding with warmer and cooler weather conditions, respectively (Wójtowicz and Wójtowicz, 2020).…”
Section: Engineering Pennycress To Confer High Oleic Seed Oil Phenotypesmentioning
confidence: 99%